Synthesis and Evaluation of Starch Acetate as Microencapsulating Agent for Controlled Release of Carbamazepine - Chowdary, K.P.R.; Subba Rao, Malluru (Asian Journal of Chemistry, 2010)
The objective of the study is to synthesize starch acetate, a new starch based polymer and to evaluate for its application as microencapsulating agent for controlled release of carbamazepine. Controlled release formulations are needed for carbamazepine to avoid its erratic absorption, fluctuating plasma concentrations and associated toxicity. Starch acetate with a degree of acetyl substitution of 2.72 could be synthesized by acetylation of potato starch with acetic anhydride. Starch acetate microcapsules of carbamazepine were prepared by an industrially feasible emulsification-solvent evaporation method and the microcapsules were evaluated for controlled release. The starch acetate microcapsules prepared are spherical, discrete, free flowing and multi nucleate monolithic type. Microencapsulation efficiency was in the range 80-87 %. Carbamazepine release from the microcapsules was slow over 24 h and depended on core:coat ratio, wall thickness and size of the microcapsules. Drug release from the microcapsules was analyzed by Fickian diffusion mechanism. Good linear relationship was observed between wall thickness of the microcapsule and release rate. Starch acetate was found suitable as a new microencapsulating agent and the starch acetate microcapsules exhibited good controlled release characteristics. Carbamazepine release from starch acetate microcapsules, MC3 fulfilled the official (USP 30) release requirement prescribed for carbamazepine extended release tablets and these microcapsules were found suitable for once daily administration of carbamazepine.